Elementa Chemiae : Quae Anniversario Labore Docuit, in Publicis, Privatisque Scholis, Volume 2 - Boerhaave, Herman (Apud Casparaum Fritsch, 1732)
Herman Boerhaave (1668-1738) was a Dutch botanist, chemist, and physician. Boerhaave introduced a quantitative approach to medical training and was the first to integrate chemistry into the medical curriculum; he is regarded as the founder of clinical teaching and of the modern academic hospital. Boerhaave is also credited as the first physician to isolate the chemical urea from urine and to put thermometer measurements into clinical practice. Elementa chemiae is Boerhaave’s textbook of chemistry. The work was published in several languages and editions throughout Europe. This edition is the first octavo printing and the only edition published in Latin at Leipzig. The first volume contains parts on the history and theory of chemistry. The second volume pertains to teachings of physical chemistry, especially heat, air, Lavoisier’s caloric theory, Boyle’s law, and preparative operations in chemical experimentation. Digitized pages of this volume include the front matter and the volume’s engraved plates.
Keywords: Chemistry--Study and teaching; Boerhaave, Herman, 1668-1738; Chemistry--Experiments; Chemistry, Physical and theoretical; Clinical chemistry